Callimachus' Puzzle About Diodorus - Marko, Vladimír (Organon F, 1995)
The author tends to emphasize that there are almost the three reasons to analyse Callimachus' epigram about Diodorus (Pfeiffer fr. 393, 1-4): First of all, the date of this epigram shows us that it represents the earliest information about Diodorus doctrine. Second, another support of its authenticity could be found in fact that this epigram expressing part of the atmosphere following, and also remaining after, discussing the Diodorian topics. Third, its philosophical relevance, usually minimised in classical literature, could be found in those facts that it could show the way out in many today dilemmas about his philosophical claims and support some of our contemporary assumptions about its logical conception, as well as that of space, time, and meaning of statements. The author defends a position that it is necessary to develop well-grounded and methodologically relevant base covering the historical reconstruction and the interpretation of ancient logical theories.